Design, synthesis, and structure-activity relationship of novel RIPK2 inhibitors. (1st November 2022) - Wu, Shuwei; Xu, Liben; Wang, Xinhui; Yang, Qing; Wang, Jingrui; He, Sudan; Zhang, Xiaohu
Graphical abstract: The derivative 17 is obtained from the prodrug 5 (GSK2983559) by using a cyclization strategy and structural optimization. Compound 17 displays a high affinity for RIPK2 (Kd = 5.9 nM) and no affinity for RIPK1 (Kd >30, 000 nM). Compound 17 exhibits favorable in vitro safety profiles and significantly suppresses inflammatory cytokine production in both cells and animal model. Highlights: A series of RIPK2 inhibitors based on a novel tricyclic scaffold is reported. Compound 17 binds to RIPK2 with high affinity (Kd  = 5.9 nM). Compound 17 exhibits low inhibition of CYP isozymes. Compound 17 displays excellent metabolic stability in human liver microsomes. Compound 17 blocks MDP-induced IL-6 in mouse model. Abstract: The NOD1/2 (nucleotide-binding oligomerization domain-containing protein 1/2) signaling pathways are involved in innate immune control and host defense. NOD dysfunction can result in a variety of autoimmune disorders. NOD-induced generation of inflammatory cytokines is mediated by receptor-interacting protein kinase 2 (RIPK2), which has been considered as a promising therapeutic target. Herein, we disclose the design, synthesis, and SAR study of a series of RIPK2 inhibitors. The lead compound 17 displayed a high affinity for RIPK2 (Kd  = 5.9 nM) and was capable of inhibiting RIPK2 kinase function in an ADP-Glo assay. In vitro DMPK studies showed that compound 17 had good metabolic stability and no CYP inhibition. Compound 17 effectively suppressed inflammatory cytokine production in both cells and animal model.